Sistem Pendukung Keputusan Penerimaan Dana Bantuan Jaminan Kesehatan Masyarakat Untuk Keluarga Miskin Menggunakan Metode Fuzzy Topsis - Cucu Handayani; Syaghil Farhan Robbany (Jurnal ICT : Information Communication & Technology, 2019)
The data processing of the election of citizens entitled to get the public health card aid fund in Kaliwadas Subdistrict, Sumber Subdistrict of Cirebon Regency generally still use manual selection system, that is, there is no computerization in determining the people who are eligible to get the help of public health insurance card so that many problems happened at this system. The problem that often arises because the target of the recipients of the public health card is not right on target to the eligible citizens, such as people who are actually not eligible to get grants but get the grant, otherwise the less fortunate people who are entitled to receive public health card security card but did not get donation. From these problems need a system for decision making, a system that can provide recommendations as a consideration for decision making accurately and accurately. This system can support decision-making of candidates receiving health insurance cards based on predetermined criteria. In order to calculate the decision support system more accurately then used a method, namely method of Fuzzy Technique for Order Preference by Similiary to Ideal Solution (Fuzzy TOPSIS) to determine the citizens who are entitled to get public health insurance card and get the best alternative value.